The Effect of using 940 nm Diode Laser in Comparison with Endoactivator on Radicular Dentin Permeability and Smear Layer Removal (An in Vitro Study) - Ruaa M. Al-Mafrachi, Lutfi G. Awazli and Mohammed A. Al-Maliky (Iraqi Journal of Laser, 2018)
Abstract: The aim of this study is to assess the effectiveness of 940 nm diode laser in comparison to Endoactivator in elimination of smear layer in terms of radicular dentin permeability and ultra-structural changes of root canal walls by SEM evaluation. Twenty-eight single-rooted extracted lower premolars were instrumented up to size X4 (protaper Next, Dentsaply) and divided into two experimental groups according to the irrigation system, G1; activated by EndoActivator and G2; activated by Diode laser 940 nm, CW mode, 1.7 W. Afterward, the roots were made externally impermeable, filled with 2%methylene blue dye, divided horizontally into three segments representing the apical, middle, and coronal thirds then examined under stereo- microscope. Using analytical software, the root section area and dye penetration area were measured, and then, the percentage of net dye penetration area was calculated. Additionally, scanning electron microscope investigations were accomplished. The non-parametric Mann-Whitney U test was done and showed significant difference between the two experimental groups over the three root thirds and the dye penetration in diode laser group was significantly higher over the whole root length compared to the Endoactivator group. Scanning electron micrographs of diode laser group showed a distinctive removal of smear layer with preservation of the annular structure of dentinal tubules, while EndoActivator group produced uneven removal of smear layer, in efficient cleanliness especially in the apical third.